Обзор палеарктических родов семейства Eurytomidae (Hymenoptera, Chalcidoidea) - Зерова, М.Д. (Збірник праць Зоологічного музею, 2018)
Приведены данные, характеризующие объем и морфобиологические особенности палеарктических родов семейства Eurytomidae, дана оригинальная таблица для определения родов семейства, а также приведены данные по хозяевам и распространению палеарктических родов сем. Eurytomidae. Приведено відомості щодо обсягу та морфобіологічних особливостей родів Еигуіотісіае, дана таблиця для визначення палеарктичних родів евритомід, а також приведені дані щодо господарів та поширення палеарктичних родів родини Eurytomidae. The data of morphological and biological peculiarities, trophical association and geographic distribution of 17 palearctic eurytomid genera are discussed. A key to Palearctic genera of the Family Eurytomidae is provided. This key includes seventeen genera and one subgenus from family Eurytomidae which occure in Palearctic zoogeografical region. The key complete earlear publicated keyes including some genera which arc dcscribed last time. Some more the trophic connections and destribution in Palearctic for all genera is given. Except of genera key, the key of species groups in genus Eurytoma is provided. In genus Eurytoma we distinguish 14 species group which differs by morphological and biological peculiarities as soon as by trophic associations. Material discussed in this paper is preserved in collection of Chalcid wasps in Institute of Zoology National Academy of Sciences of Ukraine (Kiev).